Radon Concentration in Urban Areas in the North and West of Morocco - A. Tayebi; M. El-Maghraoui; M. Tayebi; C. El-Mahjoub (Atom Indonesia, 2023)
Radon is a colorless, odorless radioactive gas produced by the decay of uranium and radium. It is the second cause of cancer of the lungs after smoking. It has been present in Earth's crust since the creation of Earth. Uranium-rich rocks in the deep crust are the main source of radon. Its emanation from the ground surface varies from one point to another depending on the physical characteristics of the terrain crossed as observed in this study between North and West Morocco. A dosimetric study of those emanations was performed by using the LR-115 solid-state nuclear track detector (SSNTD) which was subsequently processed by techniques developed and calibrated in the laboratory. The study revealed high concentrations of this gas in confined spaces at ground level and, in particular, in basements and less-ventilated ground floor rooms. In order to reduce these concentrations of radon and the probability of carcinogenic attacks by these accumulations of this gas, it is recommended to ventilate these premises well. Good air circulation allows the removal of this harmful gas.